Avaliação da aprendizagem no Ensino Superior: tendências da produção acadêmica no campo de Ensino de Ciências no Brasil e de Educação em Portugal (2002 A 2019) - Miguel, Kassiana da Silva (2021)
Evaluating learning is an important moment at different school levels since it reinforces the relevance of developing academic research, in order to investigate knowledge about the complexity of this topic, which cannot be simplified, in an attempt to minimize gaps that have persisted during the XXI century, in the educational scope. Thus, this study aims at theorizing about the main trends in academic production regarding learning assessment in Higher Education, from 2002 to 2019, published in Science Teaching journals in Brazil and about Education in Portugal. This research applied methodological procedures characterized as meta analysis (BICUDO, 2014), of a qualitative nature (FLICK, 2009), supported by bibliographic research methods (OLIVEIRA, 2014; BARROS; LEHFELD, 2014), in the state of art (ROMANOWSKI; ENS, 2006; FERREIRA, 2002; FATINATO; FREITAS, 2018) and in the grounded theory (CHARMAZ, 2009). It has been observed that, despite the development was fulfilled, concerning the academic research on learning assessment in Higher Education during the last 17 years, the researches development and publication on the subject are still at the beginning. Therefore, we worked, by theorization, to identify factors that can be decisive in this process, which can influence the development and consolidation of this kind of studies and researches in different areas of knowledge. In this case, the trends pointed out in this investigation show a promising scenario regarding the importance of new debates, studies and research on this subject, especially with regard to: the development and publication expansion of research on learning assessment in Higher Education; Transposition of academic research results and indications on teaching materials; Understanding by researchers, professors, managers and academics, assessment as an integrating element of teaching and learning process; Promoting collaborative study and research groups related to the educational process; the importance of more investigations, developed at the school and university contexts; Preparation of research questions and objectives that aim at finding out the evaluative practice, and conceptualization of educational phenomena to contribute on new perspectives and innovations, both conceptual and practical.